074. Pulmonary Lacunae Due to Chemotherapy-Induced Pneumothorax in Metastatic Breast Cancer: A Rare Case Report and Review of Literature - Indiwirawan, Luthfi; Budiwinata, Winardi (JBN (Jurnal Bedah Nasional), 2024)
Background : Chemotherapy plays a major role in treating breast cancer patients who develop hematogenous spread or disseminated metastase. Spontaneous pneumothorax is a rare complication of chemotherapy and is commonly associated with chemosensitive tumours such as germ-cell tumours, lymphomas, and sarcomas and rarely with lung and gynaecological malignant disease. Pneumothorax seems to occur 2–7 days after chemotherapy treatment and can be unilateral or bilateral. To present the rare case of a A 56-year-old woman with breast cancer on chemoterapy who had secondary pneumothorax after undergo chemotherapy and treated with chest tube insertion. Methods :  Clinical and imagery review of a secondary pnuemothorax after several chemoterapy outlined in case report also review of literature. Results : The patient underwent a chest tube insertion and hospitalized 10 days. She was discharged and responds well to therapy. Conclusion: This is the case of secondary penumothorax due to chemoterapy in breast cancer patient. The mechanisms involved in chemotherapy-related pneumothorax have been proposed because of tumor necrosis inducing the formation of a fistula. Our patient underwent chest tube insertion and other pharmacology therapy to decreased patient her complaint.